Correlation between microorganisms and flavor of Chinese fermented sour bamboo shoot: Roles of Lactococcus and Lactobacillus in flavor formation. (December 2022) - Chen, Caixia; Cheng, Guiguang; Liu, Yaping; Yi, Yongxin; Chen, Dongjie; Zhang, Lu; Wang, Xuejiao; Cao, Jianxin
Abstract: Sour bamboo shoot is a popular traditional fermented vegetable in southern China. The current study aims to clarify the relationship among physicochemical properties, flavor, and microbial compositions of sour bamboo shoots during fermentation. Four organic acids (OAs) were considered to be the main acids in sour bamboo shoots. At least 7 volatile compounds (OAV >1) were identified as the characteristic aroma substances, especially p -cresol, which accounted for the sour odor of sour bamboo shoots. The microbial community showed that Firmicutes and Proteobacteria were the dominant phyla, while Lactococcus and Lactobacillus were the dominant genera in sour bamboo shoots. Correlation analysis indicated that Firmicutes positively correlated with p -cresol, phenol, 2-methoxy-phenol, malic acid, total titratable acidity (TTA), and some OAs. Lactococcus was positively correlated with phenol, 2-methoxy-phenol, benzyl alcohol, TTA, some OAs, and amino acids (AAs). This study provided a theoretical basis for screening indigenous aroma-producing microorganisms as the starter of sour bamboo shoots. Graphical abstract: Image 1 Highlights: Phenols, alcohols and acids were dominant volatile compounds in sour bamboo shoots. P -cresol was the characteristic volatile compound in sour bamboo shoots. Firmicutes and Proteobacteria were the main microbial phylum in sour bamboo shoots. Lactococcus was highly associated with phenol, 2-methoxy-phenol, and benzyl alcohol.